The good research guide - Denscombe, Martyn ([S.l.] : Open University Press, 2007)
As a best-selling introductory book on the basics of social research, The Good Research Guide provides an accessible yet comprehensive introduction to the main approaches to social research and the methods most commonly used by researchers in the social sciences. This edition has been updated to account for recent developments in the field such as: The emergence of mixed methods approaches Increased use of internet research More frequent use of methods such as triangulation and focus groups Developments in research ethics Written for anyone undertaking a small-scale research project, either as part of an academic course or as part of their professional development, this book provides: A clear, straightforward introduction to data collection methods and data analysis Explanations of the key decisions researchers need to take, with practical advice on how to make appropriate decisions Essential checklists to guide good practice This book is perfect for the first-time researcher looking for guidance on the issues they should consider and traps they should avoid when embarking on a social research project.
Keywords: Research--Methodology; Social sciences--Methodology; Social sciences--Research